2017
DOI: 10.1002/mds.27082
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic deep brain stimulation for orthostatic tremor: A multicenter international registry

Abstract: Deep brain stimulation of the ventral intermediate nucleus was, in general, safe and well tolerated, yielding sustained benefit in selected patients with medically refractory orthostatic tremor. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
3
24
2
Order By: Relevance
“…A total of 14 AEs was reported in 13/18 patients (72.2%), consisting in 1 skin infection over IPG, 2 surgical revisions due to cervical pain and lead dislocation, 1 generalized tonic-clonic seizure 3 days after surgery, 2 transient paresthesia, 2 gait ataxia, 1 unilateral foot dystonia, 1 case of dizziness and 4 cases of speech difficulties. Stimulation frequency varied from 130 to 185 Hz, intensity from 1.5 to 4.0 V, and pulse width from 60 to 90 sec (Table 2) [4250]. …”
Section: Resultsmentioning
confidence: 99%
“…A total of 14 AEs was reported in 13/18 patients (72.2%), consisting in 1 skin infection over IPG, 2 surgical revisions due to cervical pain and lead dislocation, 1 generalized tonic-clonic seizure 3 days after surgery, 2 transient paresthesia, 2 gait ataxia, 1 unilateral foot dystonia, 1 case of dizziness and 4 cases of speech difficulties. Stimulation frequency varied from 130 to 185 Hz, intensity from 1.5 to 4.0 V, and pulse width from 60 to 90 sec (Table 2) [4250]. …”
Section: Resultsmentioning
confidence: 99%
“…A summary of patient clinical and demographic data for 17 OT patients who underwent DBS was recently published by Merola et al12 in a multicenter international registry, while a summary of the target coordinates and programming parameters in 12 OT patients was recently published by Lehn et al11 The two cases presented herein are the first two OT cases reported to respond favorably to asleep VIM DBS. The targeting method was identical to that used when treating upper extremity tremor: 25% the distance from posterior commissure to anterior commissure, 10.5 mm lateral to the wall of the lateral ventricle at the midcommissural plane.…”
Section: Discussionmentioning
confidence: 96%
“…Previous publications have reported the favorable response of medically refractory OT to thalamic VIM DBS surgery carried out in an awake patient, with better sustained benefit with bilateral DBS than with unilateral stimulation 312. A summary of patient clinical and demographic data for 17 OT patients who underwent DBS was recently published by Merola et al12 in a multicenter international registry, while a summary of the target coordinates and programming parameters in 12 OT patients was recently published by Lehn et al11 The two cases presented herein are the first two OT cases reported to respond favorably to asleep VIM DBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the evidence for involvement of the cerebello-thalamo-cortical network in OT, as suggested by the neuroimaging studies discussed above, some clinicians have been motivated to assess the possible beneficial effects of deep brain stimulation (DBS) of the VIM nucleus of thalamus in patients with medically refractory primary OT. 27 30 In a recently published international, multicenter study aimed at evaluating the efficacy of thalamic DBS in 17 medically refractory OT patients, Merola et al 31 reported that DBS of the VIM nucleus of the thalamus is safe, well tolerated, and yields sustained benefit in a majority of the patients so treated. Although the benefit with DBS in these cases does not provide direct information about the pathogenesis of OT, these observations further support the cerebello-thalamo-cortical network hypothesis.…”
Section: Resultsmentioning
confidence: 99%